Soil Pollution with Heavy Metals - Maria VLAD; Gelu MOVILEANU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2010)
In this paper was studied soil pollution with heavy metals (copper, chrome, manganese, lead, zinc, cadmium, nickel) caused by the municipal waste from landfill. The level of soil pollution depends on rain regime which usually brings in soil the air pollutants but in the same time washes as the soil determining the pollutants transport through the emissary. Mean value of the collected samples in four different points situated close to the landfill, were represented in the graphs and related to Maximum Admissible Concentration values. There were ascertained leads, zinc, nickel, cadmium, cation concentrations bigger than admissible values.